PERANAN UNIT OPERATION DALAM MEMPERSIAPKAN PEMBERANGKATAN PESAWAT UDARA PADA MASKAPAI PENERBANGAN DI BANDARA SOEKARNO HATTA, JAKARTA - Evaf Maulina (JURNAL MITRA MANAJEMEN, 2022)
Operational units immediately involved in the preparation of the aircraft for departure, as well as the unit in charge of the aircraft's preparation while on the ground or on the airside, require appropriate facilities and infrastructure to assist and smooth the daily work process. This unit also necessitates the hiring of qualified individuals to ensure that the job that has been outlined in the work processes is carried out correctly. Keyword: Unit Operation, Ground Handling